Outside Conventional Forms: Religion and Non-Religion in Estonia - Remmel, Atko (Religion and society in Central and Eastern Europe, 2015)
The paper focuses on the features that have influenced current religious landscape of Estonia, considered one of the most secularized countries in the world, and its “special path” to secularization. To explain the ‘irregularities’ demonstrated by the sociological surveys, the paper argues for a situational and inclinational approach to the study of (non)religiosity as the majority of religious phenomena remain outside the conventional frames of religious commitment centered on religious belief and belonging.